A Comparative Study of the Decomposition Products of Iron(III) Peroxy-chromate - Richharia, Neelam; Bajpai, Rita; Tiwari, Sanjay; Tiwari, B.M.L. (Asian Journal of Chemistry, 2016)
Iron(III) peroxy-chromate has been prepared by the interaction of iron(III) chromate with anhydrous hydrogen peroxide. The ratio of Fe(III : Cr(IV) : peroxy-oxygen has been found to be 1 : 2.79 : 1.30, which supports the formulation of studied peroxy-chromate as Fe2(Cr2O10)3. For this, the water, silver(I) oxide and lead dioxide, decomposition products of the prepared iron(III) peroxy-chromate, have been investigated with the help of ion-exchange resins, electronic absorption, IR, pH-metric and colorimetrictechniques.